Toxic Response of Daphnia magna to Microcystis aeruginosa - Wu, Hao; Jiang, Min; Zhu, Zheng-Guo; Zhao, Yan; Qu, Rui; Liu, Jin-Jin (Asian Journal of Chemistry, 2013)
Microcystins produced by M. aeruginosa have adverse effects on aquatic organisms and are recognized as potent stress factors in aquatic ecosystems. As an ideal model organism for aquatic toxicology research, D. magna has been selected in this study to assess the adverse effects of microcystins in incipient stage of cyanobacteria M. aeruginosa bloom. The results show that the contents of total protein in D. magna of experimental groups have no obvious difference compared to the control groups during seven days, nor do the other physiological and biochemistry indicators such as albumin, alkaline phosphatase and total cholesterol. However, the alanine aminotransferase and glycerin trilaurate in D. magna decrease rapidly in experimental groups. Large amounts of lipid droplets are also observed in the body of D. magna fed on M. aeruginosa. The RAPD assay of genome experiment indicates both microcystin-LR and M. aeruginosa will induce DNA changes at the second and third generation of D. magna. The results suggest that M. aeruginosa will affect the D. magna on both DNA and metabolism.